Estimation of acoustic transmission loss for carbon honey comb panel with melamine foam. (December 2022) - Zai, Behzad A; Sami, Saad; Waseem, Muhammad; Rehman, Tanzeel Ur
In this paper, the acoustic noise reduction of aluminum honeycomb/carbon face sheet sandwich panel with Melamine Foam (MF) lining of variable thicknesses (25 mm & 50 mm) is numerically estimated and then experimentally verified using impedance tube based on transfer matrix method. The presence of carbon face sheets and MF lining can have a significant impact on the Transmission Loss (TL). The impedance tube can measure the TL for frequency range of 64 Hz–6.2 kHz. A conventional, two-microphone impedance tube, is connected to a sample holder downstream of the first microphone pair and a section downstream of the sample holder that accommodates a second pair of microphones. The Finite Element Analysis and experimental results are compared and found in good agreements. The TL levels for each layer of material is estimated prior to have TL for combined structure. Furthermore, the optimized insulation foam thickness of 50 mm is obtained based on required acoustic parameters.